2015
DOI: 10.1055/s-0035-1554277
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Neurography of the Lumbar Plexus at the L4–5 Disc: Development of a Preoperative Surgical Planning Tool for Lateral Lumbar Transpsoas Interbody Fusion (LLIF)

Abstract: Introduction The lateral transpsoas approach for lumbar interbody fusion (LLIF) is a minimally invasive surgical technique that is now frequently used to treat common spinal disorders. During LLIF, the course of the plexus within the surgical corridor places it at risk for iatrogenic intraoperative injury. Several previous studies have suggested that the risk of neurological injury during LLIF is higher at L4–L5. Current imaging techniques of assessing the proximity of neural tissue to the L4–L5 disc space hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
7
0
2
Order By: Relevance
“…Another study examined the course of the lumbar nerve plexus using magnetic resonance neurography (MRN) in 35 patients. MRN imaging clearly showed the lumbar nerve plexus at the dorsal half of L4-5 on the left and right sides 16) .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another study examined the course of the lumbar nerve plexus using magnetic resonance neurography (MRN) in 35 patients. MRN imaging clearly showed the lumbar nerve plexus at the dorsal half of L4-5 on the left and right sides 16) .…”
Section: Discussionmentioning
confidence: 97%
“…Complications of bowel injury after LLIF surgery at L3-4 and L4-5 have been reported 1) . Older patients with a low BMI favorably show the existence of a retrorenal colon, possibly because of low adipose tissue content in the retroperitoneal space 13,15,16) . In these circumstances, it is more difficult for the bowel to move ventrally and easier to approach the anterior pararenal extraperitoneal space.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded reviews, spinal cord studies and animal or in vivo studies. Our review identified a total of 35 articles: 24 DTI studies and 11 diffusionweighted MR neurography studies [31][32][33][34][35][36][37][38][39][40][41] . The number of lumbar nerve DTI studies has sharply increased in recent years ( Fig.…”
Section: Trends In Clinical Mr Neuroimaging Of Lumbar Nervesmentioning
confidence: 99%
“…The use of DWI based neurographic sequences has demonstrated several advantages over conventional morphological neurographic studies (9,18,28,29). The strength of these techniques relies on providing functional and quantitative information, allowing a correct understanding of the normal physiology of PN and the pathophysiological processes that underlie the different conditions involving PN, with potential influence to improve their diagnosis and therapy monitoring.…”
Section: Clinical Scenariosmentioning
confidence: 99%